A Germanium Bolometer for the Far Infrared - Tumber, Adrian James (My University, 1968)
A technique has been developed for constructing low temperature germanium bolometers for use as detectors in the far infrared. Their performance has been evaluated both by measuring their responsivity and noise and comparing these with the theoretical values and also by using the bolometer in conjunction with a far infrared spectrophotometer to obtain spectra showing the theoretical resolution of 0.11 cm^-1 at 55 cm^-1 expected for this instrument.
Keywords: Germanium, bolometer, Far Infrared, temperature, resolution